Design of a Home-Based Jaundice Therapy System Powered by Arduino - Hussein, Aslam Najeh; Alwan, Baneen Bahlool; Khudair, Hassan Hussein; Hussain, Hassanein Abbas; Talib, Zainab Neamah (American Journal of Biomedicine and Pharmacy, 2024)
This paper focuses on the development and evaluation of a device for the treatment of neonatal jaundice. Neonatal jaundice is a common condition in newborns caused by elevated levels of bilirubin in the blood, which can lead to serious complications if left untreated. Phototherapy is a standard treatment modality for neonatal jaundice, involving the exposure of the baby’s skin to specialized lights that help break down excess bilirubin. However, existing phototherapy devices have limitations in terms of efficacy, safety, and accessibility. In this paper, we present the design and implementation of our device, which aims to address these limitations and provide a more effective and user-friendly solution for neonatal jaundice treatment. The device incorporates advanced UV light technology and features a compact and portable design suitable for use in various healthcare settings. We conducted a series of experiments to evaluate the performance of our device, including measurements of UV intensity and comparative analyses with existing phototherapy devices used in several hospitals. The results of our experiments demonstrate that our device achieves higher UV intensity levels compared to other phototherapy devices, making it potentially more effective in reducing bilirubin levels in newborns. Furthermore, our device exhibits favourable characteristics such as portability, ease of use, and compatibility with existing healthcare infrastructure. These findings suggest that our device has the potential to significantly improve the outcomes of neonatal jaundice treatment and enhance the quality of care for newborns. Future work includes conducting clinical trials, optimizing the device design, establishing standardized protocols, and promoting global accessibility and adoption of effective phototherapy solutions. By addressing these future research directions, we aim to advance the field of neonatal jaundice management further and contribute to better health outcomes.